The European industrial challenge and the Italian NRRP - Paolo Maranzano; Mario Noera; Roberto Romano (PSL Quarterly Review, 2021)
This paper investigates the consistency of the Italian National Recovery and Resilience Plan with the economic and industrial policy objectives outlined in the "Next Generation EU" plan and the European Commission's New European Industrial Policy. We analyze official policy documents in order to highlight some macroeconomic impact indicators with respect to the mission-based allocation of European and national financial resources. The New European Industrial Strategy is particularly challenging; industrial objectives outline a structural challenge capable of reshaping much of the industrial structure and strengthening critical value chains, especially in key sectors. Such an economic challenge requires clear strategic priorities in order to guide the economic transition. In this context, the Italian plan is particularly relevant since it brings together the largest share of European resources. The essay analyzes in detail the allocation of resources of the Italian NRRP, which-while formally adhering to the European guidelines-fails to address the priorities outlined by the EU-wide industrial strategy.
Keywords: E60; E61; E65; 330; NGEU; economic policy; structural change; sectors